Effect of Nb or Ta Interlayer on Microstructure and Mechanical Properties of Graphite/Ti6Al4V Alloy Joints. Issue 4 (29th January 2021) - Ma, Xinjian; Mao, Yangwu; Duan, Yu; Deng, Quanrong; Wang, Geming; Wang, Shenggao
Abstract : Graphite/Ti6Al4V (TC4) joining has been conducted with Cu–Ti–Ni filler and refractory metal (Nb or Ta) interlayer. Microstructural characterizations reveal that defect‐free interfaces are obtained among the refractory metal interlayer, fillers, and substrates, suggesting favorable interfacial bonding in the joints. The diffusion and dissolution of Nb or Ta atoms into the molten fillers occur during joining, leading to the formation of (Ti, R) solid solution ([Ti, R]ss, R = Nb, or Ta) in the filler layers and thickness decrease in the interlayer. Two filler layers adjacent to the interlayer primarily consist of Ti–Cu, Ti–Cu–Ni intermetallics, and (Ti, R)ss. A Ti‐rich diffusion layer and a thin TiC‐containing layer exist near TC4 and graphite substrates, respectively. The joints brazed with Nb and Ta interlayers exhibit shear strength of 2 1.0 ± 2.7 MPa and 20.2 ± 3.1 MPa, respectively, both higher than those without interlayer, implying that the introduction of refractory metal interlayer may benefit the joint stress relaxation by its intermediate coefficient of thermal expansion and high ductility. The joint strength with Nb interlayer is slightly higher than that with Ta interlayer, mainly attributed to the relatively lower elastic modules and yield strength of Nb. Abstract : Graphite/Ti6Al4V joining is conducted with Cu–Ti–Ni filler and refractory metal (Nb or Ta) interlayer. Effect of Nb or Ta interlayer on microstructure and mechanical properties of joints is investigated. Diffusion and dissolution of Nb or Ta atoms into molten fillers occur. The joints brazed with Nb and Ta interlayers exhibit higher shear strength than those without interlayer.